Recent advances in antibacterial applications of metal nanoparticles (MNPs) and metal nanocomposites (MNCs) against multidrug-resistant (MDR) bacteria. Issue 6 (3rd June 2019) - Alavi, Mehran; Rai, Mahendra
ABSTRACT: Introduction : In recent years, multidrug resistance (MDR) in bacteria has drastically increased and has posed a great threat to the human health. This problem has generated an urgent need to search alternatives for the treatment of MDR bacteria. It has been proved that metal nanoparticles (MNPs) and metal nanocomposites (MNCs) possess remarkable antimicrobial potential, and hence can be used in alternative therapy. Areas covered : This review is aimed to discuss recent reports on antibacterial activities of MNPs and MNCs against MDR bacteria. Expert opinion : Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter baumannii, Klebsiella pneumoniae, Serratia marcescens, Streptococcus pneumoniae, and Staphylococcus epidermidis are important pathogenic bacteria which have shown MDR against a wide range of conventional antibiotics. In this context, effects of MNPs and MNCs on these pathogens have demonstrated considerable efficacy. Several mechanisms concerning activity of MNPs and MNCs against pathogenic bacteria which are mainly dependent on type of their precursors and treated bacterium have been investigated. In addition, many studies have been made on antibacterial activities of these nanomaterials with similar and different results.